2023
DOI: 10.1038/s41420-023-01330-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage triggers squamous metaplasia in human lung and mammary cells via mitotic checkpoints

Abstract: Epithelial transdifferentiation is frequent in tissue hyperplasia and contributes to disease in various degrees. Squamous metaplasia (SQM) precedes epidermoid lung cancer, an aggressive and frequent malignancy, but it is rare in the epithelium of the mammary gland. The mechanisms leading to SQM in the lung have been very poorly investigated. We have studied this issue on human freshly isolated cells and organoids. Here we show that human lung or mammary cells strikingly undergo SQM with polyploidisation when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Interestingly, a previous study using human airway cells and a mouse model reported that TGF‐β induced airway squamous metaplasia via Smad signalling, which was blocked by an anti‐TGF‐β antibody [31]. The other study, using human lung and mammary cells, reported that DNA damage has the potential to drive squamous metaplasia via mitotic checkpoints [32]. Similar mechanisms may underlie salivary gland metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study using human airway cells and a mouse model reported that TGF‐β induced airway squamous metaplasia via Smad signalling, which was blocked by an anti‐TGF‐β antibody [31]. The other study, using human lung and mammary cells, reported that DNA damage has the potential to drive squamous metaplasia via mitotic checkpoints [32]. Similar mechanisms may underlie salivary gland metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Both chronic smoking and FBA have been shown to induce epithelium squamous metaplasia, it might be unclear if the cherry pit is only responsible factor, and smoking is additional factor contributed to the event. Juan et al showed that DNA damage has the potential to drive the squamous metaplasia via mitotic checkpoints, opening novel molecular candidate targets for lung squamous cell carcinoma ( 22 ). Furthermore, atypical adenomatous hyperplasia is prescribed as risk factor for lung cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed this DNA-induced differentiation response as an automatic mechanism that maintains the integrity of the tissue and at the same time, cleanses it of damaged precancerous cells. There is also evidence suggesting that the DDR pathways drive the epidermoid phenotype, even in the lung, thus controlling epithelial cell fate [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%